Quality of Life as A Predictor of Happiness and Life Satisfaction - Novianti, Langgersari Elsari; Wungu, Esti; Purba, Fredrick Dermawan (Faculty of Psychology, Universitas Gadjah Mada, 2020)
This study aimed to find correlations between the quality of life, happiness, and life satisfaction of the general population of Bandung city. There were 370 participants with averageage of 20.7 years, mostly male (55.7%) and with a secondary level of education (SMP-SMA; 57.0%) who completed three questionnaires: (i) WHOQOL-BREF to measure quality of life, (ii) Happiness Thermometer to measure happiness, and (iii) Self-Anchoring Cantril Striving Scale to measure life satisfaction. Multiple linear regression tests were used with happiness and life satisfaction as dependent variables and quality of life as an independent variable. The results showed that the psychological and physical domains of quality of life were significant predictors of happiness and satisfaction of life, where the psychological domain proved significant in predicting all four-time points: happiness today (Î²=0.039; p<0.05), happiness throughout life (Î²=0.043; p<0.05), current life satisfaction (Î²=0.034; p<0.05) and life satisfaction five years from now (Î²=0.017; p<0.05). Physical domain was similar to psychological except for current life satisfaction (Î²=0.029; 0.023; 0.014; p<0.05). The environmental domain had been shown to predict happiness throughout life significantly (Î²=0.019; p<0.05) and life satisfaction five years from now (Î²=-0.015; p<0.05). The social domain was not found to be a significant predictor. It can be concluded that improving the psychological and physical function of Indonesian people and their environmental conditions will lead them to a happier and more satisfying life.